2021
DOI: 10.12688/f1000research.52546.1
|View full text |Cite
|
Sign up to set email alerts
|

Better survival of patients with oligo- compared with polymetastatic cancers:  a systematic review and meta-analysis of 173 studies

Abstract: Background: The modern concept of oligometastatic (OM) state has been initially developed to describe patients with a low burden of disease and with a potential for cure with local ablative treatments. We systematically assessed the risk of death and relapse of oligometastatic (OM) cancers compared to cancers with more diffuse metastatic spread, through a meta-analysis of published data.  Methods: PubMed, the Cochrane Library, and EMBASE were searched for studies reporting prognosis of patients with OM solid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…http://dx.doi.org/10.17632/8kycvdnp6v.1. 10 Data are available under the terms of the Creative Commons Attribution 4.0 license (CC-BY 4.0).…”
Section: Data Availabilitymentioning
confidence: 99%
“…http://dx.doi.org/10.17632/8kycvdnp6v.1. 10 Data are available under the terms of the Creative Commons Attribution 4.0 license (CC-BY 4.0).…”
Section: Data Availabilitymentioning
confidence: 99%
“…Moreover, oligometastatic cancers exhibit an intermediate state between localized and systematic metastasized disease, reflecting an early stage in the chain of progression, where the tumors have a constrained capacity for widespread metastasis [1]. In a metaanalysis of 173 studies by Petrelli et al, patients with oligometastatic disease had superior prognosis than those with widespread polymetastatic tumors [2]. Therefore beside their distinct biological behavior, these tumors represent a unique clinical entity, with a potential for long-term disease control or even cure [1,2].…”
Section: Introduction -Defining Oligometastatic Disease Stagementioning
confidence: 99%
“…In a meta-analysis of 173 studies by Petrelli et al , patients with oligometastatic disease had superior prognosis than those with widespread polymetastatic tumors [2]. Therefore beside their distinct biological behavior, these tumors represent a unique clinical entity, with a potential for long-term disease control or even cure [1,2]. The classification system of oligometastatic tumors was formed through a Delphi consensus led by Guckenberger et al in 2020, reflecting their different biological features [3 ▪▪ ].…”
Section: Introduction – Defining Oligometastatic Disease Stagementioning
confidence: 99%
“…In recent years, oligometastasis (OM), a unique intermediate state between locally confined disease and systemic metastatic disease [ 30 ], has attracted increasing attention. It was first proposed by Hellman and Weichselbaum in 1995 to describe a subset of states with a limited number and sites of metastases [ 31 ], emphasizing relatively restricted tumor burden and better outcomes than that of polymetastasis [ 32 , 33 ]. Dorn et al [ 34 ] showed that in breast cancer, patients with oligometastasis had a higher 5-year (59.6 % vs. 11.6 %) and median survival (107 vs. 22 months, p = 0.001) compared to those with polymetastases.…”
Section: Introductionmentioning
confidence: 99%